(untitled) (Revista de Estudos da Linguagem, 2024)
This study aims to support the translation of Bildungstrieb as “formative drive” in Wilhelm von Humboldt’s On the diversity of linguistic constructions and its influence in the spiritual development of mankind, 1836. The taken direction was given by the Neo-Kantian philosopher Ernst Cassirer (among others), for whom Humboldt mobilizes essential concepts from Immanuel Kant’s philosophy; thus, through philological comparison between Kant and Johann Friedrich Blumenbach’s critical fortunes and Humboldt’s work, the concept of “formative drive” was mapped as one that marked the debate on organized bodies in the investigation of nature. To theorize the formation of the articulated sound, Humboldt takes inspiration from Kant and Blumenbach’s debate, for whom the autonomy of living matter and the status of its development answer to the formative drive – a natural force that unites the mechanical one, as described by Newtonian laws, to the teleological one, in which something is cause and effect at the same time. As a result, teleology is fundamental to Humboldt’s reflection on the articulated sound, thus opposed to the arbitrary nature of the linguistic sign. Furthering Humboldt’s proximity to Kant and Blumenbach’s debate on nature, in Humboldt’s work there are metaphors of the organism; metaphors became the focus of the philosopher Johann Georg Hamann critics to Kant in one of the first reflections on language’s role in the Kantian critical project (reflections adhered by Humboldt). Thus, the trajectory Kant-Blumenbach/Hamann-Humboldt explains Humboldt’s usage of a metaphor of organism to assert language’s status as the formative organ of thought.